2019
DOI: 10.3389/fncel.2019.00476
|View full text |Cite
|
Sign up to set email alerts
|

P2Y6 and P2X7 Receptor Antagonism Exerts Neuroprotective/ Neuroregenerative Effects in an Animal Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder characterized by decreased dopamine bioavailability in the substantia nigra and the striatum. Taking into account that adenosine-5’-triphosphate (ATP) and its metabolites are intensely released in the 6-hydroxydopamine (6-OHDA) animal model of PD, screening of purinergic receptor gene expression was performed. Effects of pharmacological P2Y6 or P2X7 receptor antagonism were studied in preventing or reversing hemiparkinsonian behavior and dopaminergic def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 59 publications
(79 reference statements)
1
42
0
Order By: Relevance
“…Animal models of PD show that the P2X7 receptor is involved in disease development, especially in microglial cell activation. In an animal model of nigrostriatal injury induction by 6-OH dopamine (6-OHDA), a toxic dopamine analog, striatal gene expression of the P2X7 receptor gradually increased over 5 weeks after injury (Oliveira-Giacomelli et al, 2019). Neuroprotective effects of P2X7 receptor antagonism were observed after pretreating animals with A-438079.…”
Section: Parkinson's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Animal models of PD show that the P2X7 receptor is involved in disease development, especially in microglial cell activation. In an animal model of nigrostriatal injury induction by 6-OH dopamine (6-OHDA), a toxic dopamine analog, striatal gene expression of the P2X7 receptor gradually increased over 5 weeks after injury (Oliveira-Giacomelli et al, 2019). Neuroprotective effects of P2X7 receptor antagonism were observed after pretreating animals with A-438079.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Treatment of neuronal-differentiated SH-SY5Y cells, an in vitro model of dopaminergic neurons, with BBG protected cells from 6-OHDA-induced synaptotoxicity and death (Carmo et al, 2014;Oliveira-Giacomelli et al, 2019). In addition, assays with wild-type and α-synuclein mutants of microglial cells showed that α-synuclein activated microglial P2X7 receptors, inducing NADPH oxidase, modulating the PI3K/AKT signaling pathway and increasing oxidative stress (Jiang et al, 2015).…”
Section: Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The protective effect of BBG treatment against 6-OH-DA-induced hemiparkinsonian symptoms including microglial activation in the substantia nigra [ 186 ] and striatum [ 187 ] was repeatedly confirmed. BBG attenuated the oxidative stress (lipid peroxidase and superoxide dismutase activities), as well as the deterioration of mitochondrial integrity (changes in mitochondrial membrane potential and mitochondrial complex-I, II, III and IV-activities) [ 187 ].…”
Section: Parkinson’s Disease (Pd)mentioning
confidence: 99%
“…Oliveira-Giacomelli et al (2019) tested the effects of P2Y6 and P2X7 in preventing or reversing PD behavior and dopaminergic levels in male Sprague Dawley rat models using 7 µg/µL of 6-OHDA dose injected unilaterally into the right midforebrain of two-month-old male Sprague Dawley rats. The motor changes confirmed after the 1st week of 6-OHDA lesion, behavioral analysis data showed no significant rotational behavior before 6-OHDA lesion, and significant behavioral changes were observed only after 1st, 3rd, and 5th week of 6-OHDA lesion where the number of rotations which increased in a time-dependent manner [ 94 ].…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%